A STUDY ON DIFFERENT TYPES OF PANDU ROGA WITH SPECIAL REFERENCE TO SOME COMMON LABORATORY PARAMETERS (International Journal of Ayurveda and Pharma Research, 2017)
Pandu is a disease which is explained by almost all our Acharyas where the color of the body of the patient alters like the polen grain of the Keteki flower. Due to its similarity we can co- relate the Pandu roga with the disease anaemia. On the basis of pathophysiology and morphology of RBC different types of anaemia has been classified and accordingly treatment is given. Similarly there are five types of Pandu roga along with its specific Cikitsa for its types has been explained in the Samhitas. This work has been done to establish any relationship of different types of Pandu roga with some common laboratory parameters which are done to diagnose anaemia. For the study 500 patients of Pandu roga are clinically diagnosed and some common laboratory parameters were investigated. Finally a conclusion has been drawn showing different ranges and findings of the laboratory parameters corresponding to the types of Pandu Roga.